INSTITUTIONAL CAPACITY OF LOCAL INSTITUTIONS AND ITS IMPLICATION FOR LOCAL ECONOMIC DEVELOPMENT: THE CASE OF ADAMA CITY, ETHIOPIA (Journal of Governance and Development (JGD), 2021)
Success in local economic development (LED) strategy is closely related to the strength of available institutional capacity in the area. That means, LED as an alternative development strategy is successful and sustainable only if there are capable local institutions in the area. To this end, the major objective of this article is to investigate the institutional capacity of local organizations or institutions and its implication for the successful implementation of LED as a viable alternative development strategy in Adama city. Mixed research method was employed to achieve the objective of the study. Survey questionnaire and interview were used to collect data. Simple random sampling technique was used to administer the questionnaires. Purposive and convenience sampling techniques were used for qualitative data collection. Narrative technique was used to analysis qualitative data. Both descriptive and inferential analysis methods were employed to analyze data obtained through survey questionnaire from 158 respondents with the help of SPSS software applications. The findings of the study reveal that local institutions in Adama city have suffered from serious institutional capacity constraints. The adoption of LED as the only development strategy is not beneficial in areas where local institutions have limited institutional capacity. So, the study recommends that LED as an alternative development strategy could be practiced in the study area in parallel with the top-down development approach which can be gradually replaced after institutional capacity deficits are properly addressed.